TAG4VD: a game for collaborative video annotation - Pinto, José Pedro (2018)
Creating descriptive labels for videos is an important task, with application in video retrieval, Web accessibility and computer vision. However automatic creation of such labels is difficult and, alternatively, having professionals manually describing content is too expensive. Engaging end-users in the process of describing multimedia assets may lead to good results and enables creating the sense of participation which is currently one of the key factors to attract customers to a service. The existing approaches are highly successful in terms of number of engaged players and number of collected labels, but hardly create comprehensive tag sets, contributing both with generic or too narrow meaning tags. "Games With A Purpose" are one of the approaches that have been used in an attempt to create comprehensive video descriptions by harnessing the intelligence of human players and have them contributing and collaborating towards a common goal that is recognized if successful. This paper describes a game which implements two mechanisms for collecting data via human-based computation games. Tags introduced by registered players, in a given timecode, are validated based on a collaborative scoring mechanism that eliminates irregular annotations. Additionally, a voting mechanism that enables players to endorse or refuse existing tags, provides an extra instrument to guarantee the quality of the annotations.